Model Penegakan Hukum Terhadap Kasus Korupsi Dana Pembangunan Puskesmas Waigete di Kecamatan Waigete Kabupaten Sikka - Agustina Putri Patricia; Aksi Sinurat; Darius Antonius Kian (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This study uses empirical juridical research, which is research with field data as the main source of data, such as the results of interviews and observations, with the aim of analyzing and describing the law enforcement model for cases of corruption in the development funds of the Waigete Health Center. as well as identifying and analyzing factors that hinder law enforcement in the case of corruption of the Waigete Health Center development funds. The results of the discussion in this study show that, (1). The Waigete Health Center uses the Due Process Model which emphasizes the need to ensure that every individual has the right to be treated fairly and has access to an independent court including investigation, prosecution, and fair justice. and the right to appeal, but with strict legal procedures, this model slows down the process of resolving cases. The crime eradication process focuses more on the interests of the rights of suspects than on the public interest, so according to researchers in the process of resolving corruption cases, this model is not appropriate to use because it emphasizes justice and human rights but also has the potential to slow down the legal process. (2). The factors that hinder law enforcement in handling corruption cases of the Waigete Health Center development fund consist of two factors, namely internal factors, namely the lack of prosecutors who slow down the law enforcement process and reduce the effectiveness of case handling, and external factors, namely the slow examination process and the loss calculation process so as to hinder law enforcement.